2017
DOI: 10.1002/tee.22379
|View full text |Cite
|
Sign up to set email alerts
|

Review of DFIG wind turbine impact on power system dynamic performances

Abstract: Recently, the variable-speed wind turbine with doubly fed induction generator (DFIG) has drawn significant attention because of its many advantages such as small power converter rating, the ability to control the output power, etc. Nevertheless, the large penetration of DFIG wind turbines may affect the power system dynamics. This paper provides a general review of the DFIG wind turbine's impact on power system dynamic performances such as frequency stability, transient stability, small-signal stability, and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 117 publications
(141 reference statements)
0
29
0
Order By: Relevance
“…The DFIG effect on power system dynamics is divided into four main categories which are voltage stability, small-signal stability, transient stability, and frequency stability [16]. Voltage stability is defined as the capability of power systems to maintain nominal voltages at all buses after disturbances.…”
Section: E Dfig-based Wecs Effects On Power Systemsmentioning
confidence: 99%
“…The DFIG effect on power system dynamics is divided into four main categories which are voltage stability, small-signal stability, transient stability, and frequency stability [16]. Voltage stability is defined as the capability of power systems to maintain nominal voltages at all buses after disturbances.…”
Section: E Dfig-based Wecs Effects On Power Systemsmentioning
confidence: 99%
“…The dynamic performance evaluation and stability analysis of DFIG with their control techniques in WIPS has been analysed by many researchers as presented in [6,9]. Most of these have presented the advantage of independent control, a consequence of grid disturbance and WECS on interconnected power systems as well as maximum power point tracking (MPPT) and fault ride through behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Wind power generation has become one of the most important renewable energy power generation technologies in the world (Marugan et al, 2018;Tian et al, 2018a). However, it is found that the randomness of wind speed has a serious impact on the stability of power system after grid connection (Ngamroo, 2017). At present, there are two ways to solve this problem: the first one is to increase the installed capacity of wind power and the rotating reserve capacity of conventional units to restrain the impact of wind power system on the grid, but this will increase the operating costs of the system (Koivisto et al, 2016).…”
Section: Introductionmentioning
confidence: 99%